2015
DOI: 10.1016/j.ijsolstr.2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

A stress-concentration-formula generating equation for arbitrary shallow surfaces

Abstract: a b s t r a c tAnalytical understanding of how stress concentrates is invaluable. An equation that generates stress concentration formulas is derived and shown to apply very well to a number of shallow irregularities on surfaces, for the plane stress conditions and to a first-order approximation. Under shallow conditions, for any first-order Hölder-continuous surface function f ðxÞ, the derived equation is:where H is the Hilbert transform and f 0 ðxÞ is the spatial derivative of f with respect to the independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 20 publications
1
9
0
1
Order By: Relevance
“…Analyzing a sinusoidal surface perturbation of a stressed solid at the macrolevel, Gao (1991) has shown that even a slightly undulating surface can generate significant stress concentration that can induce fracture before the bulk stress reaches a critical level. Similar results have been analytically obtained for cycloid-shaped surfaces ( Chiu and Gao, 1993 ), arbitrary weakly curved surfaces ( Grekov and Kostyrko, 2015;Grekov and Makarov, 2004;Medina, 2015;Medina and Hilderliter, 2014;Vikulina et al, 2010 ), and interfaces ( Grekov, 2004( Grekov, , 2011Grekov and Kostyrko, 2013 ).…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Analyzing a sinusoidal surface perturbation of a stressed solid at the macrolevel, Gao (1991) has shown that even a slightly undulating surface can generate significant stress concentration that can induce fracture before the bulk stress reaches a critical level. Similar results have been analytically obtained for cycloid-shaped surfaces ( Chiu and Gao, 1993 ), arbitrary weakly curved surfaces ( Grekov and Kostyrko, 2015;Grekov and Makarov, 2004;Medina, 2015;Medina and Hilderliter, 2014;Vikulina et al, 2010 ), and interfaces ( Grekov, 2004( Grekov, , 2011Grekov and Kostyrko, 2013 ).…”
Section: Introductionsupporting
confidence: 84%
“…Quite a number of them are reviewed in Bashkankova et al (2015) . Recently, based on this method, Medina and Hilderliter (2014) and Medina (2015) have derived stress concentration formulas for different slightly curved surfaces at the macrolevel and Mohammadi et al (2013) have presented derivations that relate both a periodic and a random roughness to the effective surface elastic behaviour. Unlike all cited papers, our perturbation technique, based on the original equation in complex potentials, similar to (14) , leads either to the same explicit equation or the same integral equations in an approximation of any order.…”
Section: Boundary Perturbation Proceduresmentioning
confidence: 99%
“…The maximum stress concentration occurs at the base of the dimple. Based on the analytical solution for stress concentration factor in sinusoidal shallow surface, 41,42 the maximum stress concentration factor, K t , can be related to depth and width of the dimple as Kt=1+4πaw. This gives us the value of K t as 1.15. Then, from Equation 3), the K f was calculated to be 1.12.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of zero-order approximation, F 0 = 0 and we arrive to the homogeneous equations (13), which have only trivial solution τ (0) (x 1 ) = 0 corresponding to the problem of bimaterial with perfectly flat interface Γ (0) and piecewise uniform stress state:…”
Section: Fig 1 a Model Of Bimaterials With Slightly Perturbated Intementioning
confidence: 99%
“…In past decades, a number of studies have been conducted, where the stress concentration caused by surface or interface irregularities was considered [6][7][8][9][10][11][12][13][14]. But these studies have been focused on the case of macroscale roughness and didn't take into account the surface/interface stress, assuming it insignificant compared to the external loading.…”
mentioning
confidence: 99%